Agrofoods for sustainable health benefits and their economic viability - Zakia Khanam; Irshad Ul Haq Bhat (John Wiley & Sons Ltd., 2017)
The presence of beneficial phytochemicals in agrofoods has a deep impact on both quality and control, and increases their value in the global market. This chapter focuses on the chemical constituents present in agrofoods along with the marketable strategies to generate profitable business and provide health benefits to society. Therefore various diseases can be regulated or prevented not by consuming medicine but by choosing healthier food options. Food-related transnational corporations and mobilization of food with and within nations have played a great role in the globalization of agrofood. The chapter discusses the baseline information on phytochemicals, their effect on health and the market value of some commonly consumed fruits and vegetables. In developing countries, in addition to production and preservation, the phytochemical information for end users can add new avenues to market value of agricultural-based food.